Power and impoliteness in Hancock action movie - Favian Reswara Sani; Suhandoko Suhandoko (Englisia: Journal of Language, Education, and Humanities, 2020)
This study examined the strategies employed by the main character in the Hancock movie named John Hancock to attack his interlocutors’ face, the way the recipients responded to his impoliteness, and how he used impoliteness to exercise his power. By using content analysis to draw inferences from utterances in the movie transcript, the study found that positive impoliteness is the most frequent strategy used by Hancock due to its abusive nature and withhold impoliteness is the least used due to its unlikeliness to damage the interlocutor’s face. Also, the study found that the recipients used all strategies to respond to Hancock’s impoliteness, except abrogation and dismissing. At the same time, apart from Hancock’s use of impoliteness to exercise power, such as to appear as superior, to get power over actions, and to dominate the conversation as Beebe (1995) noted, this study found that silence is also a way to exercise power to maintain control of undesired situations. The finding adds substantially to our understanding that silence as an impoliteness strategy might also serve the purpose of exercising power. This, of course, is open to debate and further research would verify or contradict this claim.